A molecular genetic approach to the aetiology of cardiovascular disease in South Africa with reference to progressive familial heart block - Brink, Paul Andries (Stellenbosch : Stellenbosch University, 2012)
Dissertation (D.Phil.) -- University of Stellenbosch, 1997.